Traumatic Injuries Requiring Simultaneous Emergent Operative Procedures, Knife Wounds to the Top of the Skull and the Abdomen - L Ray Matthews; Moungar Cooper; David Carney; Omar Danner; Jonathan Nguyen; Keren Bashan Gilzenrat; Carolyn Moore; Kahdi Udobi; Ed Childs; Peter Rhee; Assad Taha (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
The simultaneous commencement of operative interventions by two or more surgical teams in the multiply injured patient is gaining more acceptance. We describe a rare case of concomitant penetrating injuries to the brain, chest and abdomen that required an orchestrated immediate approach and resulted in a good outcome. Both injuries were life threatening. A coordinated effort between Trauma Surgery and Neurosurgery working simultaneously produced an excellent outcome for this patient.